Smart farming: IoT-enhanced greenhouse control system - Mohd Ismadi, Muhammad Hafiy Naim; Miswan Hanis, Muhammad Nur Ezzuddean; Muhammad Akram, Amir Syarif; Mohamad Zaidi, Nur Iqmal Hasif (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
The IoT-Enhanced Greenhouse Control System is a sustainable, cost-effective solution designed to optimize small-scale agriculture, particularly for household and urban farming. Using an ESP32 microcontroller, the system integrates sensors to monitor temperature, humidity, soil moisture, and light intensity, while actuators such as fans, water pumps, and LED indicators automate responses to environmental changes. Powered by solar energy, the system ensures energy efficiency and environmental sustainability. Real-time data is logged into Google Sheets and display through a web-based dashboard, enabling users to monitor and control greenhouse conditions remotely. This reduces manual labor, enhances precision farming and maintains ideal conditions for plant growth. By addressing challenges like inconsistent crop growth, inefficient water usage, and reliance on traditional energy sources, the system supports sustainable farming practices and food security. Its unique integration of IoT with renewable energy provides a scalable and affordable solution for urban households, community farms, and small-scale agricultural enterprises. Additionally, the system’s user-friendly interface allows easy operation, making it accessible to non-expert users. With significant socio-economic and environmental impacts, including reduced carbon footprints and resource conservation, the project demonstrates strong commercialization potential in the growing smart agriculture market, catering to the rising demand for sustainable and automated farming solutions